Planning and Budgeting of Tourism Sector in West Nusa Tenggara - Bayu Kharisma; Adhitya Wardhana; Ade Marsinta Arsani; Haposan Indra Wesly Pasaribu (Economics Development Analysis Journal, 2022)
West Nusa Tenggara is one of the central province of tourist destinations in Indonesia. This study aims to identify the consistency between planning and budgeting of the tourism sector in West Nusa Tenggara Province. Consistency analysis is done by analyzing the vision, mission, program, and budget. In addition, it compares planning and budgeting according to variance and percentage change between documents. The results showed that the level of consistency of the RPJPD and RPJMD as well as the RKPD in West Nusa Tenggara Province could be categorized as "excellent". In addition, this consistency is reflected in the total variance and standard deviation. Meanwhile, the analysis of the RPJMD and Renstra shows that there is a mismatch between the vision and mission and is categorized as "bad". Finally, the analysis of the consistency of budget values in the RPJMD and DPA shows that there are inconsistencies in planning and budgeting. Furthermore, the comparison between the target and the realization shows that in 2021, West Nusa Tenggara will not be able to achieve its target. These results indicate that the local government should evaluate the tourism program in the planning and budgeting process to obtain optimal results.